2018
DOI: 10.1111/bjhp.12306
|View full text |Cite
|
Sign up to set email alerts
|

What do self‐efficacy items measure? Examining the discriminant content validity of self‐efficacy items

Abstract: Self-efficacy items vary in terms of their content validity with only some of the items assessed providing 'pure' measures of the self-efficacy construct. Item wording should be considered during study design to avoid misinterpretation. Statement of contribution What is already known on this subject? For decades, questions have been raised relating to the content validity of self-efficacy scales, with suggestions of possible construct contamination. Previous studies have shown that manipulation of the wording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…However, while an item such as ‘I am sure I can exercise, even when it is raining outside’ is meant to measure one’s strength of capability, the statement could be interpreted in two ways, because ‘can’ has a literal interpretation (If I really wanted to, I can exercise in bad or good weather) and a figurative interpretation (I cannot exercise in bad weather, because it would be uncomfortable) (Williams, 2010). This has been demonstrated in research that shows the effect that holding motivation constant has on PBC and SE evaluations (Rhodes & Blanchard, 2007; Rhodes & Courneya, 2003, 2004), as well as in the confounding of motivation with standard SE items, as shown in a recent discriminant content validity study (Burrell, Allan, Williams, & Johnston, 2018). This effect has also been replicated in studies using vignettes, or a small set of instructions to prime participants to consider the literal interpretation of the words ‘can’ and ‘cannot’, and not the figurative interpretations, when completing PBC/SE questionnaires (Lithopoulos, Grant, Williams, & Rhodes, 2020; Rhodes, Williams, & Mistry, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…However, while an item such as ‘I am sure I can exercise, even when it is raining outside’ is meant to measure one’s strength of capability, the statement could be interpreted in two ways, because ‘can’ has a literal interpretation (If I really wanted to, I can exercise in bad or good weather) and a figurative interpretation (I cannot exercise in bad weather, because it would be uncomfortable) (Williams, 2010). This has been demonstrated in research that shows the effect that holding motivation constant has on PBC and SE evaluations (Rhodes & Blanchard, 2007; Rhodes & Courneya, 2003, 2004), as well as in the confounding of motivation with standard SE items, as shown in a recent discriminant content validity study (Burrell, Allan, Williams, & Johnston, 2018). This effect has also been replicated in studies using vignettes, or a small set of instructions to prime participants to consider the literal interpretation of the words ‘can’ and ‘cannot’, and not the figurative interpretations, when completing PBC/SE questionnaires (Lithopoulos, Grant, Williams, & Rhodes, 2020; Rhodes, Williams, & Mistry, 2016).…”
Section: Introductionmentioning
confidence: 74%
“…We developed a self-efficacy scale for nurses, and it showed high internal consistency and reliability (Cronbach’s alpha 0.79). The content validity of our self-efficacy items was good because the formulation of items was based on the review by Burrell et al [ 23 ], which showed that it is valid to measure self-efficacy starting with the statement “I am confident that…”. The face-validity of the items was also good as the statements describe nurses’ essential everyday practices in oral health care among older people and are valid in the work of geriatric home care nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The self-efficacy items were formulated by A-MS and M-LL. The content validity of the self-efficacy items was based on a review of Burrell [ 23 ], who proposed that by asking “I am confident that…” is a valid measure of self-efficacy. The items consist of home care nurses’ essential everyday practices in oral health care among older people and are valid in the work of geriatric home care nurses.…”
Section: Methodsmentioning
confidence: 99%
“…Two methods are currently available for assessing content validity, namely, the Content Validity Index (CVI) (Lynn, 1986) and Discriminant Content Validity (DCV) (Johnston et al, 2014). Whilst CVI has been used to assess content validity of health outcome measures, DCV has been used to assess the content validity of theoretical process variables (Bell et al, 2017;Burrell et al, 2018;Gardner, Abraham, Lally, & de Bruijn, 2012;Johnston et al, 2014) and theoretical domains (Cane, O'Connor, & Michie, 2012;Huijg, Gebhardt, Crone, Dusseldorp, & Presseau, 2014), as well health outcome measures (Dixon, Johnston, Mcqueen, & Court-Brown, 2008;Dixon, Pollard, & Johnston, 2007;Pollard et al, 2006;Schmitt et al, 2013).…”
Section: Methods Of Assessing CV and Dcvmentioning
confidence: 99%
“…Clearly, success in making use of such evidence depends on valid labelling of the theoretical construct and this process may be derailed by misleading classification of measures. For example, some self‐efficacy items have been found to tap ‘motivation’ as well as self‐efficacy (Burrell, Allan, Williams, & Johnston, ) and if used as a basis for designing an intervention might result in the selection of less appropriate techniques than might be achieved if determinants of the behaviour were identified using measures with content validity.…”
Section: Definitions Of Validity (Adapted From the Apa)mentioning
confidence: 99%